(untitled) (Scientific journal of the Fergana State University, 2025)
The article provides an in-depth analysis of the significance and various methods of assessment in foreign language teaching. Diagnostics and assessment are presented as essential tools for monitoring learners’ progress, identifying their needs, and enhancing the efficiency of the educational process. Formal assessment, such as standardized international tests (IELTS, TOEFL), allows for an objective evaluation of learners’ grammatical knowledge and core language skills. Informal assessment, on the other hand, is flexible and supports identifying learners’ weaknesses during lessons, enabling tailored approaches to their needs. Formative assessment focuses on tracking learners’ continuous development and helps teachers adjust their lessons accordingly, while summative assessment plays a vital role in evaluating final outcomes. The article highlights the motivational aspects of formative assessment, including providing constructive feedback to enhance learners’ educational progress. The importance of integrating formal and informal assessments, along with formative and summative approaches, is emphasized as a means of improving the quality of education and fostering learners’ competencies. Additionally, employing diagnostic methods is noted as a key factor in enhancing teachers’ pedagogical skills. The assessment process effectively adapts education to learners’ needs, contributing to overall educational quality improvement.